The Role of Lactobacillus reuteri DSMZ17648 for Helicobacter pylori eradication therapy (Review of literature and advisory council resolution, February 28, 2018) - V. T. Ivashkin; O. P. Alekseyeva; A. Yu. Baranovsky; Ye. K. Baranskaya; Ye. V. Beloborodova; T. A. Kolesov; N. V. Korochanskaya; K. . Lang; T. L. Lapina; I. V. Mayev; M. V. Mokshina; D. L. Nepomnyashchy; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of review. To analyze the options of application of Lactobacillus reuteri DSMZ17648 (Pylopass™) within Helicobacter pylori eradication. Summary. H. pylori eradication therapy is considered as one of the optional spheres for clinical application of probiotic medications. According to available data certain strains of probiotics are effective in decreasing of gastrointestinal adverse effects rates, associated with eradication therapy while the other can potentiate the efficacy of H. pylori eradication itself. L. reuteri strain DSM17648 which was chosen from over 700 wildtype strains of Lactobacillus spp. possess the ability for selective adhesion to H. pylori in vivo in the gastric media. DSM17648 strain of L. reuteri form coaggregates with various H. pylori strains and serotypes both in vivo and in vitro. It was revealed that lyophilizate of this strain (PylopassTM) blocks adhesion of H. pylori to epithelial cells as well. Clinical trials demonstrate the effect of PylopassTMon gastric mucosa colonization by H. pylori according to the 13C urea breath test data and as well the increase in H. pylori eradication rate when the productis added the to triple therapy modes. Conclusion. Potential of PylopassTM combination to various H. pylori eradication therapy modes is a subject offutnet multicenter randomized clinical trials for assessment of optimal combination to antibiotic drugs, treatment duration and adverse effect rates. The value of monotherapy by this metabiotic at chronic H. pyloriassociated gastritis is a subject of further studies.